Strawberry GRN forever: insights into the transcriptional regulatory network controlling strawberry fruit ripening and quality - Martín-Pizarro, Carmen; Sánchez-Gómez, Carlos; Meco, Victoriano; Urrutia, María; Pillet, Jeremy; Lucas Reina, Eva; Trapero-Mozos, Almudena; Vallarino Castro, José G.; De Luis Balaguer, María Angels; Pérez-Sancho, Jessica; Bayer, Emmanuelle M.; Franco-Zorrila, José Manuel; et al. (My University, 2022)
Ripening is a critical step for the development of flavor quality in fruits. This character has significantly declined in many fleshy fruits over recent decades. This is particularly significant in strawberry (Fragaria × ananassa), where current cultivars are derived from a narrow germplasm collection. Improving fruit quality requires two important breakthroughs: 1) a precise understanding of the fruit ripening process that will allow the targeting of relevant genes, and 2) the identification of novel alleles responsible for fruit quality traits. In our project, we aim at the identification and characterization of key transcription factors (TF) involved in fruit ripening regulation and their target genes, in order to infer the Gene Regulatory Network controlling this process. Among them, we have identified two TFs belonging to the NAC (FaRIF) and the BLH9 (FaRPL) family. Functional analyses establishing stable silencing and overexpression lines support that both TFs play a critical role in the regulation of fruit ripening and development. Furthermore, using a stage- and tissue-specific transcriptome analysis, we have identified TFs specifically expressed in the external layer of ripe receptacles of F. vesca fruits, which are involved in the regulation of wax and cuticle formation. Finally, we have implemented the use of the genome-editing tool CRISPR/Cas9 in the cultivated strawberry, which we expect to open opportunities for engineering this species to improve traits of economic importance.
Keywords: TF; Frutas-Calidad-Investigación genética; Strawberry ananassa-Mejora genética; Fresas - Mapa genético; Cultivos - Ingeniería genética; Transcripción genética; Factores de transcripción; Frutas - Sabor y olor; Strawberry; Transcription Factor; Ripening